DAMPAK PANDEMI COVID-19 TERHADAP KINERJA KEUANGAN DAN HARGA SAHAM PT. SIANTAR TOP TBK - Sarida Sirait; Vanesa Berlien; Calen Calen; Richard Berlien; Kalvin Sinaga; Beatrice Nathania (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
This study aims to find out how the impact of the COVID-19 pandemic on the financial performance and stock price of PT SIANTAR TOP TBK because many companies are experiencing various obstacles in running their companies during the COVID-19 pandemic. Financial performance is important for business people because it is one of the indicators to find out how the company is. It was found that PT SIANTAR TOP did not experience a high enough impact which can be seen through several ratios which indicate that PT SIANTAR TOP was still able to run its company well even though it experienced a decline in several quarters in 2020. PT SIANTAR TOP's share price was relatively stable which can be seen from data shows that the price of PT SIANTAR TOP is stable at Rp. 8,000 to Rp. 12,000 which shows that investors are still interested in buying PT SIANTAR TOP's shares even though they are during the COVID-19 pandemic.